Cultured Horse Articular Chondrocytes in 3D-Printed Chitosan Scaffold With Hyaluronic Acid and Platelet Lysate - De Angelis, Elena; Saleri, Roberta; Martelli, Paolo; Elviri, Lisa; Bianchera, Annalisa; Bergonzi, Carlo; Pirola, Marta; Romeo, Roberta; Andrani, Melania; Cavalli, Valeria; Conti, Virna; Bettini, Ruggero; et al. (Frontiers in Veterinary Science, 2021)
Three-dimensional (3D) printing is gaining popularity in tissue engineering owing to its capability to develop complex formulations for cartilage regeneration. In the present study, horse articular chondrocytes were cultured for two and four weeks in 3D-printed chitosan (CH)-based scaffolds prepared with or without hyaluronic acid and in the presence of foetal bovine serum (FBS) or platelet lysate (PL). These 3D culture systems were analysed in terms of their capability to maintain chondrocyte differentiation in vitro. This was achieved by means of cell morphology, immunohistochemistry (IHC), and gene expression of relevant cartilage markers (Collagen type II, aggrecan, and Sox9) compared with that of a dedifferentiated phenotype (Collagen type I, Runx2). The morphological, histochemical, immunohistochemical, and molecular results demonstrated that the 3D CH scaffold is sufficiently porous to be colonised by primary chondrocytes. Thereby, it provides an optimal environment for the proliferation and synthetic activity of chondrocytes during a long culture period where a higher rate of differentiation and cellular senescence can be generally observed. Enrichment with hyaluronic acid provides an optimal microenvironment for a more stable maintenance of the chondrocyte phenotype. The use of 3D CH scaffolds causes a further increase in the gene expression of most relevant ECM components when PL is added as a substitute for FBS in the medium. This indicates that the latter system enables a better maintenance of differentiation, thereby highlighting a fair balance between proliferation and differentiation.